Managing Household Waste in Ireland: Behavioural Parameters and Policy Options - John Curtis; Seán Lyons; Abigail O'Callaghan-Platt (The Economic and Social Research Institute (ESRI), 2009)
Ireland has signed up to ambitious targets for diverting municipal solid waste from landfill. These targets are likely to be very difficult to meet without substantial changes to the way household waste is collected and managed. Data on household waste management behaviour in Ireland is scarce, and policymaking could benefit from improved data and market analysis. In this paper we use data from the EPA and CSO to estimate econometric models of household waste collection in Ireland, providing national estimates of income elasticities of demand, price elasticities where unit charges are in place, effects of imposing weight-based charging and effects of other important changes to service characteristics. These results are then used in a simulation model to illustrate the likely effects of some current policy options.
Keywords: 330; municipal solid waste; household waste management; Ireland; Abfallentsorgung; Kommunale Abfallwirtschaft; Irland